Hyperglycemia in Childhood Acute Lymphoblastic Leukemia during Induction Chemotherapy - Nengcy Erlina Tasik Rerung; Cahyadi, Andi; Nur Rochmah; Maria Christina Shanty Larasati; Andarsini, Mia Ratwita; Muhammad Faizi; IDG Ugrasena; Bambang Permono (PT Dexa Medica, 2021)
Introduction: Hyperglycemia is a well-known adverse effect of the corticosteroids and asparaginase given during induction chemotherapy for pediatric acute lymphoblastic leukemia (ALL). ALL is a type of hematologic malignancy with high incidence in the childhood. The aim of this study is to investigate the impact of hyperglycemia during induction chemotherapy in childhood ALL. Methods: This prospective study was done in Dr. Soetomo hospital from January to April 2018. The subject was newly diagnosed as ALL under the age of 18 years, treated with Indonesian childhood ALL 2013 protocol (standard risk (SR) group and high risk (HR) group). Hyperglycemia was defined as at least two separate random plasma glucose levels >200 mg/dL, which was evaluated before and during induction chemotherapy. Statistical analysis using Paired T-test for parametric and Wilcoxon test for nonparametric. Results: Thirty-three children were enrolled, 18/33 boys with mean age 5.8 (SD 3.78) years, compromised as ALL-L1 30/33. They were treated with ALL-HR 19/33 and ALL-SR 14/33. In overall groups, the mean random blood glucose level significantly increased from 108 (SD 21.3) mg/dl to 147 (SD 48.1) mg/dl, (mean difference 38.67 mg/dl; 95% CI 18.08 to 59.26 mg/dl, p=0.008). In SR group, there was a significant increase of mean random blood glucose level from 102 (SD 13.5) mg/dl to 133 (SD 37.3) mg/dl, (mean difference 31.8 mg/dl; 95% CI 8.78 to 54.8 mg/dl; p=0.01). In HR group, the mean random blood glucose level increased from 113 (SD 51.9) mg/dl to 165 (SD 25.4) mg/dl, (mean difference 51.9 mg/dl; 95% CI 18.6 to 85.2 mg/dl, p=0.004). Conclusion: Blood glucose level is significantly increase during induction chemotherapy in both SR and HR Indonesian childhood ALL 2013 protocol.